Ethnopharmacological Study: Documentation and Quantitative Analysis of Traditional Knowledge of Medicinal Plant Use by the Sasak Tribe in Lombok to Treat Digestive disorders - Rahmawati; Citra Dewi Salasanti; Nur Azizah; Ertati Suarni; Delladari Mayefis (Fundamental and Applied Research in Medicine and Allied Sciences Indonesia, 2026)
The Sasak tribe possesses rich traditional knowledge of medicinal plants for digestive disorders, yet systematic documentation remains limited. This study documented and quantitatively analyzed medicinal plants used by Sasak traditional healers for gastrointestinal diseases through a cross-sectional ethnopharmacological survey involving 120 informants across five districts on Lombok Island. Data were collected using semi-structured interviews and analyzed using Use Value (UV), Relative Frequency of Citation (RFC), Fidelity Level (FL), and Informant Consensus Factor (FIC). A total of 20 plant species from 17 families were identified, with Curcuma longa, Zingiber officinale, and Psidium guajava being the most frequently cited. High informant consensus was found for diarrhea and dysentery (FIC = 0.978) and gastritis-related disorders (FIC = 0.977). Leaves and rhizomes were the most commonly used plant parts, while decoction was the primary preparation method. A strong positive correlation between UV and RFC (r = 0.94, p < 0.001) indicates a well-structured ethnopharmacological system with promising potential for further pharmacological validation. Conservation of this traditional knowledge is strongly recommended.